FORMULASI SEDIAAN PASTA GIGI DENGAN ARANG AKTIF TEMPURUNG KELAPA (Cocos nucifera L) SEBAGAI PEMUTIH GIGI - Liana Febrianti; Desy Nawangsari; Adita Silvia F (LPPM Sekolah Tinggi Ilmu Farmasi Nusaputera, 2021)
Teeth are one of the important aesthetic factors for a person, including tooth color. The effect of tooth discoloration can cause a person's lack of self-confidence. The use of teeth whitening materials can cause side effects in the oral cavity so that the use of natural ingredients is chosen as a tooth whitener, one of which is activated charcoal. Activated charcoal has an absorption capacity of 25-100%. The purpose of this study was to determine the activity of coconut shell-activated charcoal toothpaste as a teeth whitener. This study used 20 dentures and then soaked them in coffee solution for 17 days to change the color of the teeth. Tooth color was measured using a classical Vitapan shade guide. Teeth whitening activity test was carried out for 14 days. Toothpaste was made in 4 formulas with different concentrations of coconut shell-activated charcoal in formula 1 (0%), formula 2 (6%), formula 3 (10%), and formula 4 (12%). The results of the observation showed that the preparation of coconut shell-activated charcoal toothpaste can give tooth discoloration. A statistical tests showed that coconut shell-activated charcoal toothpaste had a significant difference in activity as a natural ingredient for whitening teeth.